Management of urinary incontinence in postmenopausal women: An EMAS clinical guide. (January 2021) - Russo, Eleonora; Caretto, Marta; Giannini, Andrea; Bitzer, Johannes; Cano, Antonio; Ceausu, Iuliana; Chedraui, Peter; Durmusoglu, Fatih; Erkkola, Risto; Goulis, Dimitrios G.; Kiesel, Ludwig; Lambrinoudaki, Irene; et al.
Highlights: Urinary incontinence is the most frequent lower urinary tract symptom after the menopause. The prevalence of urinary incontinence increases with age, and estimates range from 38 % to 55 % for women aged over 60 years. Many effective treatment options exist and a tailored therapeutic approach should be used. Local estrogen administration is effective for the treatment of vulvovaginal atrophy and seems to decrease complaints of urgency incontinence. Combining therapies may enhance efficacy and decrease adverse effects. If surgery is planned, there is a need to consider voiding dysfunction and coexisting types of urinary incontinence. Abstract: Introduction: The prevalence of urinary incontinence and of other lower urinary tract symptoms increases after the menopause and affects between 38 % and 55 % of women aged over 60 years. While urinary incontinence has a profound impact on quality of life, few affected women seek care. Aim: The aim of this clinical guide is to provide an evidence-based approach to the management of urinary incontinence in postmenopausal women. Materials and methods: Literature review and consensus of expert opinion. Summary recommendations: Healthcare professionals should consider urinary incontinence a clinical priority and develop appropriate diagnostic skills. They should be able to identify and manage any relevant modifiable factors that could alleviate the condition. A wide range of treatment options is available. First-line management includes lifestyle and behavioral modification, pelvic floor exercises and bladder training. Estrogens and other pharmacological interventions are helpful in the treatment of urgency incontinence that does not respond to conservative measures. Third-line therapies (e.g. sacral neuromodulation, intravesical onabotulinum toxin-A injections and posterior tibial nerve stimulation) are useful in selected patients with refractory urge incontinence. Surgery should be considered in postmenopausal women with stress incontinence. Midurethral slings, including retropubic and transobturator approaches, are safe and effective and should be offered.